Nosocomial infection in the intensive care unit. 1997-2002. - Marta Luján Hernández; Leticia Justafré Couto; Gudelia Cuellar Gutiérrez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Fundament: The infections nosocomiales constitute an important problem of health, for what is of supreme importance to identify the epidemic situation of this. Objective: Describe the behaviour of the infections nosocomiales in the Unit of Intensive Cares. Methods: I Study descriptive retrospective carried out in the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ of Cienfuegos during the years 1997-2002. The following variables were included: hospital expenditures, cases infected by months and years, localizations, germs, deaths and procedures of more risk (ventilation mechanics, deep veined catheters and vesical catheters). Results: We check stabilization in the global rates, the cases you find inside the predicted parameters, the main localization was the breathing one with a percentage stocking of 42 in the seven investigated years, while the germ of more circulation was the Acynetobacter with an average of 27,1%. The rates of mortality associated to infection stayed low and the lethality suffered a on decreased in the studied period, however the pneumonias associated to the ventilation mechanics stayed high with an average of 24, 6 for every 1000 patient days and to the closing of the 2002 the service you will find in the area of security of the endemic channel.K